Threshold Values in German Labor Law and Job Dynamics in Small Firms: The Case of the Disability - Wagner, Joachim; Schnabel, Claus; Kölling, Arnd (IFO-Studien, 2001)
According to the German disability law, or Schwerbehindertengesetz, either six percent of all jobs in an establishment must be occupied by disabled empoyees or the firm has to pay a penalty of DM 200 per month for every job under consideration. This note reports results from the first econometric investigation of the impact of this rule on job dynamics in small firms. Based on data from the IAB Establishment Panel we find no clear-cut evidence that employment in establishments at the first threshold of the law reacts differently on demand shocks than establishments below or above the threshol
UnivIS-Import:2015-03-09:Pub.2001.rw.fbwiwi.LVS.thresh
Keywords: disability law; Threshold value; labor demand